2018
DOI: 10.1038/s41598-018-29330-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the genetic basis of breast microcalcifications and their role in metastasis

Abstract: Breast cancer screening and early stage diagnosis is typically performed by X-ray mammography, which detects microcalcifications. Despite being one of the most reliable features of nonpalpable breast cancer, the processes by which these microcalcifications form are understudied and largely unknown. In the current work, we have investigated the genetic drivers for the formation of microcalcifications in breast cancer cell lines, and have investigated their involvement in disease progression. We have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Osteopontin could be involved in the process. Silencing of osteopontin decreased the formation of hydroxyapatite in breast cancer cells in response to osteogenic cocktail . The current study demonstrated calcifications found in CNB was significantly associated with a reduced upgrade risk, suggesting the accurate sampling of targeted lesions.…”
Section: Discussionmentioning
confidence: 52%
“…Osteopontin could be involved in the process. Silencing of osteopontin decreased the formation of hydroxyapatite in breast cancer cells in response to osteogenic cocktail . The current study demonstrated calcifications found in CNB was significantly associated with a reduced upgrade risk, suggesting the accurate sampling of targeted lesions.…”
Section: Discussionmentioning
confidence: 52%
“…Among the transcriptional regulators of ADSC is SPP1, which is also secreted by adipose tissue [219]. It has been shown that SPP1 is responsible for the formation of hydroxyapatite crystals in BC cells in response to an osteogenic cocktail [220]. Furthermore, the expression of SPP1 is significantly elevated in calcified BC [221], and the expression of SPP1 also aids in bone metastasis of BC cells [222].…”
Section: Microcalcificationsmentioning
confidence: 99%
“…1C) for capturing the phenotypic differences in terms of their morphological and molecular attributes. Our previous characterization of these cell lines confirmed their distinct metastatic abilities commensurate with the stage and organ from which they were isolated [31]. Our recent investigation of the biophysical properties of these cells revealed that the LM cells are most motile and least stiff, which bestow them with unique invasive capability [8].…”
Section: Resultsmentioning
confidence: 95%